Ion and Water Molecule Distribution over Illite Particle Surface; Russian Physics Journal; Vol. 65, iss. 4 - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Wang Cailun; Khan V. A. Valery Alekseevich; Baraban A. P. Aleksandr Petrovich; Poberezhnikov A. D. Andrey Dmitrievich; Shukshina D. D. Darjya Dmitrievna (2022, 2022)
Title screen